Evaluation of the Makam Scale Theory of Arel for Music Information Retrieval on Traditional Turkish Art Music - Gedik,A.C.; Bozkurt,B.; Bozkurt, Barış; Gedik, Ali Cenk (Routledge, 2009)
Current music information retrieval (MIR) methods are specifically tailored to the needs of western music. Therefore, it is not straightforward to apply these methods to non-western musics such as traditional Turkish art music (TTAM). Western music theory plays a crucial role in MIR studies. The divergence, however, between theory and practice in traditional Turkish art music (TTAM) results in a lack of a reliable theory of TTAM on which MIR techniques can be based. This is particularly true for theories regarding pitch scales and interval structures in TTAM. In this paper, we evaluate the most influential (yet disputable) theory of TTAM, Arel theory, by means of a makam classification task, to understand whether it can provide a basis for MIR studies on TTAM in a similar way western music theory provides a basis for MIR studies on western music. It is shown that Arel theory is overall successful when applied for modality finding in TTAM and that it can be improved if small modifications are introduced following pitch values obtained from musical practice. © 2009, Copyright Taylor & Francis Group, LLC.
Keywords: [No Keyword Available]